2007
DOI: 10.1016/j.tafmec.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale approach of fatigue and shakedown for notched structures

Abstract: The aim of this paper is to analyse the fatigue phenomena in the presence of stress gradients. It is well-known that most fatigue criteria fail to predict the lifetime of components in the presence of high stress concentrations or stress gradients, as it is the case in the neighbourhood of cracks, holes notches and encountered for example in riveted or threaded structures. Proposed is a numerical approach in the framework of the high cycle fatigue domain in order to give a qualitative answer. The work starts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The authors find that the Dang Van equivalent stress and the Fatemi and Socie equivalent slip amplitude do not highlight the well know critical character of the grains at the free surface when considering high cycle fatigue behaviour. Bertolino et al (2007) use the concept proposed by Dang Van, whereby elastic shakedown of the grains can be seen as a limit for crack initiation. They therefore sought to determine, using numerical models, the critical load above which at least one grain does not elastically shakedown.…”
Section: Introductionmentioning
confidence: 99%
“…The authors find that the Dang Van equivalent stress and the Fatemi and Socie equivalent slip amplitude do not highlight the well know critical character of the grains at the free surface when considering high cycle fatigue behaviour. Bertolino et al (2007) use the concept proposed by Dang Van, whereby elastic shakedown of the grains can be seen as a limit for crack initiation. They therefore sought to determine, using numerical models, the critical load above which at least one grain does not elastically shakedown.…”
Section: Introductionmentioning
confidence: 99%
“…In other words and as numerically shown by Bertolino et al [16], when the stress gradient is high, fewer grains are subject to plastic deformation and consequently to crack initiation. On the contrary, with a uniform stress distribution over a larger scale, for example for the biggest defects, the situation is closer to the case of a smooth specimen.…”
Section: Discussionmentioning
confidence: 55%
“…Recently, Bertolino et al [16] showed, by means of microstructural simulations, that the stress gradient occurring at the notch tip can strongly influence the probability of finding a favourably oriented grain at the notch root. This leads to an average increase in the fatigue strength, which can be correlated to the intensity of the stress gradient.…”
Section: Fatigue Analysis and Gradient Effectmentioning
confidence: 99%
“…In order to capture the multi-scale behavior present at a material, numerous multi-scale modelling approaches has been proposed to fulfill different purpose of engineering applications (Li et al, 2010, Yang et al, 2014, Bertolino et al, 2007. However, in the research field of railway engineering, few investigations on wheel-rail interaction using multi-scale approach have been reported so far.…”
Section: Computational Multi-scale Coupling Strategymentioning
confidence: 99%